2011
DOI: 10.1038/ni.2085
|View full text |Cite
|
Sign up to set email alerts
|

Afferent lymph–derived T cells and DCs use different chemokine receptor CCR7–dependent routes for entry into the lymph node and intranodal migration

Abstract: Little is known about the molecular mechanisms that determine the entry into the lymph node and intranodal positioning of lymph-derived cells. By injecting cells directly into afferent lymph vessels of popliteal lymph nodes, we demonstrate that lymph-derived T cells entered lymph-node parenchyma mainly from peripheral medullary sinuses, whereas dendritic cells (DCs) transmigrated through the floor of the subcapsular sinus on the afferent side. Transmigrating DCs induced local changes that allowed the concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(304 citation statements)
references
References 37 publications
9
293
2
Order By: Relevance
“…3A), but not on cortical or subcortical LS. This is well in line with the report of Braun et al (19) who found that lymphocytes directly infused into the afferent lymphatics enter the lymph nodes preferentially via the medullary sinus, but use the SS when injected together with dendritic cells.…”
Section: Discussionsupporting
confidence: 80%
“…3A), but not on cortical or subcortical LS. This is well in line with the report of Braun et al (19) who found that lymphocytes directly infused into the afferent lymphatics enter the lymph nodes preferentially via the medullary sinus, but use the SS when injected together with dendritic cells.…”
Section: Discussionsupporting
confidence: 80%
“…Here, we considered the novel possibility that the development of an expanded network of lymphatics in and around fibrosarcomas might facilitate entry of naïve T cells from neighboring tissues via afferent lymph. In support of this hypothesis, naïve T cells have been reported in afferent lymph, albeit in lower numbers than memory cells 17. Uptake of lymph into fibrosarcomas was assessed by monitoring the accumulation of Evans Blue Dye,18 after injection of the dye into the base of the leg of a tumor‐bearing mouse (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, cortical and medullary sinuses contained T cells (data not shown) and B cells but not DCs (Fig. 6Aiii, 6Av), because very few DCs egress from LNs compared with lymphocytes (7,10,15,37,38). Because few DCs from noninflamed skin migrate to the LNs, we induced DC migration by epicutaneous application of a contact sensitizer.…”
Section: Preferential Expansion Of Cortical and Medullary Sinuses Occmentioning
confidence: 93%